2013
DOI: 10.5539/gjhs.v6n2p105
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual Syndrome Symptomatology among Married Women of Fertile Age based on Methods of Contraception (Hormonal versus Non-Hormonal Methods of Contraception)

Abstract: Introduction:Premenstrual syndrome (PMS) refers to the cyclic occurrence of a set of disturbing physical, emotional or behavioral alterations that are of sufficient severity to interfere with interpersonal relations and routine life. Normal variations in gonadal estrogen and progesterone lead to biochemical reactions in the brain, resulting in PMS symptoms. This study aims to investigate the prevalence of PMS and PMDD signs among married women of fertile age (MWFA) based on the methods of birth control.Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 35 publications
2
14
3
Order By: Relevance
“…The prevalence rate of moderate/severe PMS in our study was 36.9%. This was higher than some other studies [10, 12, 33, 36, 37]. Furthermore, our study found that 17.0% of students reported impaired family relationship related to PMS experience.…”
Section: Discussioncontrasting
confidence: 81%
“…The prevalence rate of moderate/severe PMS in our study was 36.9%. This was higher than some other studies [10, 12, 33, 36, 37]. Furthermore, our study found that 17.0% of students reported impaired family relationship related to PMS experience.…”
Section: Discussioncontrasting
confidence: 81%
“…19 Rizk, et al found PMS more in females with Emirati nationality. 23 No significant association was found between contraception use among married females and premenstrual syndrome, this is similar to results reported by Chayachinda 24 and Bakhshani, 25 while inconsistent with many others, who found OCP to decrease PMS diagnosis or severity as reported by Lopez, 26 Sadler, 17 and Maria, who found higher prevalence of the syndrome in women not using any hormonal contraceptive. 27 There was no significant association between psychiatric history and premenstrual syndrome, this result is consistent with only one study reported from USA by Joyce et al, which found past history of major depression is not related to PMS.…”
Section: Discussionsupporting
confidence: 61%
“…Not all evidence supports the use of contraceptives, but they could be considered as first-line pharmaceutical interventions for women with PMDD who also require contraception (23).…”
Section: (N943)mentioning
confidence: 99%